Drug-Induced Anaphylaxis Survey in Portuguese Allergy Departments - Faria, E (2014)
BACKGROUND AND OBJECTIVE: Drug-induced anaphylaxis is an unpredictable and potentially fatal adverse drug reaction. The aim of this study was to identify the causes of drug-induced anaphylaxis in Portugal. METHODS: During a 4-year period a nationwide notification system for anaphylaxis was implemented, with voluntary reporting by allergists. Data on 313 patients with drug anaphylaxis were received and reviewed. Statistical analysis included distribution tests and multiple logistic regression analysis to investigate significance, regression coefficients, and marginal effects. RESULTS: The mean (SD) age of the patients was 43.8 (17.4) years, and 8.3% were younger than 18 years. The female to male ratio was 2:1.The main culprits were nonsteroidal anti-inflammatory drugs (NSAIDs) (47.9% of cases), antibiotics (35.5%), and anesthetic agents (6.1%). There was a predominance of mucocutaneous symptoms (92.2%), followed by respiratory symptoms (80.4%) and cardiovascular symptoms (49.0%). Patients with NSAID-induced anaphylaxis showed a tendency towards respiratory and mucocutaneous manifestations. We found no significant associations between age, sex, or atopy and type of drug. Anaphylaxis recurrence was observed in 25.6% of cases, and the risk was higher when NSAIDs were involved. CONCLUSIONS: NSAIDs were the most common cause of anaphylaxis in this study and were also associated with a higher rate of recurrence. We stress the need for better therapeutic management and prevention of recurring episodes of drug-induced anaphylaxis.